Risk factors associated with the failure of local methotrexate combined with minimally invasive surgery for late cesarean scar pregnancy - Xiao-Tong Cheng; Yan-Song Liu; Dan-Yang Song; Xiao-Cui Nie; Yu-Shi Xiang; Ju-Min Niu (BMC Pregnancy and Childbirth)
Abstract Background This study aimed to investigate the risk factors related to the failure of initial combined local methotrexate (MTX) treatment and minimally invasive surgery for late cesarean scar pregnancy (CSP). Methods This retrospective case-control study was conducted between January 2016 and December 2023, involving patients with late CSP (≥ 8 weeks) who received local MTX injection combined with either hysteroscopic or laparoscopic surgery. Cesarean scar pregnancy was classified as type I, II, or III based on the direction of growth of the gestational sac and the residual myometrial thickness as assessed by ultrasound. Binary logistic regression analysis was utilized to identify the risk factors associated with the failure of the initial combined treatment. Results Overall, 574 patients with late CSP were included in our study. Among them, 29 patients (5.1%) experienced treatment failure with the initial local MTX combined with minimally invasive surgery, while 545 patients (94.9%) achieved successful treatment outcomes. In the univariate analysis, several potential risk factors associated with the initial combined treatment failure were identified, including baseline serum β-human chorionic gonadotropin (β-hCG) levels, type of CSP, time interval between MTX and surgery, and positive fetal heart activity before surgery. Subsequent binary logistic regression analysis revealed the following independent risk factors linked to the failure of the initial combined treatment: baseline serum β-hCG levels exceeding 94,000 IU/L [odds ratio (OR) 3.060, 95% confidence interval (CI) 1.387–6.749, P = 0.006], type III CSP (OR 3.574, 95% CI 1.147–11.135, P = 0.028), a time interval greater than seven days between MTX and surgery (OR 3.847, 95% CI 1.725–8.581, P = 0.001), and the presence of a fetal heartbeat before surgery (OR 4.405, 95% CI 1.014–19.128, P = 0.048). Conclusion The findings indicate that higher baseline serum β-hCG levels, an extended time interval between MTX and surgery, type III CSP and a positive preoperative fetal heartbeat are significant risk factors for the failure of initial local MTX combined with minimally invasive surgery in patients with late CSP. Individualized treatment strategies are recommended for these high-risk patients with late CSP.